Hubungan tingkat pengetahuan tentang gizi, peer group dan uang saku dengan pemilihan jajanan pada siswa SLTP - Laras Agitya Ratnaningtyas; Intan Wahyuni Tukiyo; Helfi Agustin (Jurnal Cakrawala Promkes, 2021)
Poor nutritional behaviour among students is the increasing of snacking proportion and the consumption unnutritious and unsafe food. The aims of the study was to know the determinants of school children's snack behavior using behavioural ecological model. This was a cross-sectional study design based on ecological models behaviour. The study was conducted at a state junior high school in Sleman Regency, D.I Yogyakarta. The sample was 80 students of 381 students. The data were analyzed by the chi-square test. The result showed that only 52.5% students had selected behaviour in snacking, 50% students had a good level of knowledge about nutrition and food security, 68.8% had a large amount of pocket money, 83.8% had breakfast habit, 70% were highly influenced by peers. There were significant relations between knowledge about nutrition and food security and breakfast habits. There were no significant relations between the amount of pocket money, peers with students' behaviour to the selection of snacks in the State Junior High School in Sleman, Special Region Yogyakarta. It is recommended for schools to strengthen their school health institutions through increasing the role of student cadres and counseling about nutrition and food safety in the provision of healthy canteens. Include content about nutrition and the consequences of consuming unsafe food, placing posters on healthy and unhealthy food in the school canteen. Schools are also advised to provide socialization to parents and students about the importance of having breakfast and bringing lunch from home.